A (bio)ética e a Odontologia: os (des)caminhos de uma formação humana - Amorim, Karla Patrícia Cardoso (2005)
The present research carried out from three national dentistry magazines published in the period between 1990 and 2004, has as a goal to analyze how bioethics has been approached in this area, not only identifying the main concerns and tendencies, but also aiming to learn how this knowledge is produced and divulged in the dentistry circuit. We have articulated a quantitative-qualitative approach, studying 2995 articles. The articles were selected and assorted in twenty thematic categories, through their titles and key words. The analysis of the empiric material shows that, although there is a growth tendency of this discussion, little has been published about this theme (1,9%). Besides, it seems that there is an arrhythmia between the present bioethic approach in dentistry and the present life demands, where the deontology and legalist focuses are predominant, seeming to correspond to the inner aspects of the profession alone. In spite of this, through the qualitative approach it was possible to identify ways to build a more complex and integral odontological formation and practice. Within the conclusions, we still point out, that, this investigation, even face to its limitations, seems to offer subsidies for reflection and further studies about the theme, working as a parameter to keep up with the evolution of the bioethic thinking in the Odontology